P–483 "It's a bigger deal for her": Understanding differences in partner involvement in reproductive health decision-making. (6th August 2021) - Grace, B; Shawe, J; Stephenson, J
Abstract: Study question: What is the level of partners involvement in family-building and reproductive health decisions? Summary answer: Level of Involvement ranges from active decision-makers and equal-partnerships to indifferent or no partners. Fertility education needs to be tailored according to level of involvement. What is known already: Partner involvement is very important in alleviating stress associated with fertility and reproductive health decisions. Recent global health policies have recognised the importance of improving knowledge and awareness of fertility and reproductive health among couples, additionally there has been a concerted effort among reproductive health groups, to improve fertility awareness. Understanding the role partners play in decision-making is therefore important in order to ensure that men and women achieve their family building intentions. In this study, we interviewed men and women, to understand partners involvement in decision-making. Study design, size, duration: The study was a qualitative component of a wider mixed methods study. We carried out 35 in-depth interviews with 15 men and 20 women. Interviewees were purposively sampled to include men and women from the reproductive age range (18–45 years) and of varying ethnic and educational backgrounds. Participants/materials, setting, methods: Interviewees were sampled from a UK cross-sectional survey on Fertility Awareness. Survey participants were recruited nationwide via online newspaper and social media adverts and of those who agreed to a follow-up interview, 35 were included this study. Interviews lasted an hour on average. Data was transcribed and analysed via framework analysis. Favourable ethical opinion was given by University College London Research Ethics Committee. Main results and the role of chance: We identified four kinds of partner involvement and impact, as follows: Drivers: These are active decision-makers who play a bigger role. The decision is usually clear and directive and are typically women. Quotes describing drives include: "Her body her rights", "I just went with her [views]", MP5 - Male, Age 38. "She carries the pregnancy, and it's a bigger deal for her so it's important for her to choose." MP1 - Male, Age 45. Sharers: In these equal partnerships, joint decisions are important. Being similarly minded and aligned is key to achieving desired family building decisions. . "It was very mutual because he'd actually been talking about it for a long time… so we were both completely ready." Female, Age 31. Neutrals: general indifference to family-building decision-making and are not as proactive as the drivers. Solo: includes individuals with no partners or those who haven't met a suitable partner at the right time or until later in life, or those for whom singleness by choice is key to their decision-making. "If I did meet the right person yeah, I would love one more child, because I've always wanted two" Female, Age 36. Limitations, reasons for caution: One of the main methodological limitations of this study is that the interviewees were self-selected, which has implications for generalisability. The results necessarily reflect the views of those who were willing to participate. Online recruitment method could result in potential bias towards respondents of higher socioeconomic status. Wider implications of the findings: To improve fertility awareness, current initiatives need to further explore the impact of partners in family-building decision-making in order to have effective campaigns which can help men and women achieve their desired fertility intentions. Trial registration number: Not applicable